Biodegradable Whey Protein Edible Films as a New BiomaterialsforFood and Drug Packaging: Whey protein edible films - Majid Javanmard, (Iranian Journal of Pharmaceutical Sciences, 2009)
Food packaging extensively uses plastic films and containers of petroleum-based polymers for their excellent functional properties and competitive price.Plastic packaging has become a central focus of waste reduction efforts, particularly in aesthetic terms of damage to flora and fauna. Presently, consumers require greater quality and longer shelf lives for their foodstuffs, while they demand a reduction in the quantity of packaging materials used. In the present study, poly-ethylenglycol (PEG), glycerol, and olive oil were incorporated into whey protein concentrate (WPC) through emulsification to produce films. Whey protein films were prepared by dispersing 10% whey protein concentrate in tap water and plasticized with different levels of glycerol, PEG or olive oil. The emulsion films were evaluated for mechanical properties, water vapor permeability (WVP) and opacity.Increasing the levels of glycerol or PEG in the films resulted in a decrease in modulus and tensile strength. Increasing glycerol content of the films at oil/protein ratios of 0.2 and 0.4 led to slight increases in elongation. Increasing the oil/proteinratio further resulted in a decrease in elongation for all films. No significant difference in WVPand opacity was observed between films made from mixtures of various proportions of whey protein concentrate-glycerol with increasing PEG (addition) at all levels of the plasticizer. These results suggest that a whey proteinbased edible films is a viable alternative packaging process for food and improvement of shelf life.